The Postures of Wabi-Sabi as Perpetuated on Ibuse Masuji’s Carp - Pasopati, Rommel Utungga; Listyaningsih, Listyaningsih; Wulandari, Siti; Ohei, Sugisaka (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2024)
Literature is inseparable from the culture of its intrinsic and extrinsic meanings. It is proved on wabi-sabi, as finding simple perfectness in imperfectness, which has been embraced by Japanese people since 13th century. Carp is a short story by Ibuse Masuji that underlines uneasiness to let go a deceased person that has been befriended with for a long time. The fish of carp is a symbol of despair, but then it changes to a hope when the main character makes up his mind to be sincere in allowing his deceased friend to go. Then, how is wabi-sabi perpetuated on Ibuse Masuji’s Carp? Through qualitative method on cultural studies, this paper highlights condition of wabi-sabi as underlined in that story. Perfectness could not be found if any imperfectness is not well-appreciated. Any happiness could not be found if sadness is still held tightly. Appreciating death means knowing how valuable life is. The fish in this story is not merely an animal, but symbol of belonging that should be let go as the real owners has passed away too. In conclusion, wabi-sabi is exposed in this short story to tell how death is about imperfectness, but the freedom beyond any life is the perfection itself.